Perancangan Layout Gudang Bahan Kemas di PT. X dengan Menggunakan Pendekatan Metode Class Based Storage - Suci Oktri Viarani; Ira Novela; Nurike Oktavia (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2023)
Product layout in the warehouse is a design to arrange product storage facilities by analyzing product movements to realize efficiency and effectiveness in warehouse operational processes starting from receiving, storing and shipping products to consumers. This research was conducted at the Packaging Materials Warehouse at PT.X. Problems that occur in this packaging material warehouse occur when storing products, the operator will immediately store the product on an empty shelf. In addition, the placement of products contained in this warehouse is placed not adjacent to similar products. Based on this, this study aims to design the layout of the warehouse to make it easier for operators in the process of receiving, storing and shipping products in the warehouse, so as to minimize the distance of moving products. In the research, the approach used is the Class Based Storage method. Based on the results and discussion, it was concluded that the grouping of goods in the packaging materials warehouse of PT. X uses the class based storage method which is divided into 3 classes based on the product input-output process. Class A for the fast moving product category (80%, 10% items), Class B for the slow moving product category (15%, 15% items) and Class C for the non-moving product category (5%, 75% items). Based on the calculation of the total mileage, the distance traveled has decreased by 49.63% or a decrease in distance of 208.032.5 m.